The role of communication in interpersonal relationships at work - Oliveira, Adilson Vagner de; Faccenda, Davi Lira; Castro, Felipe Vieira; Silva, Josenilda Maria da; Sousa, Vivian Maria Santos de (Seven Editora, 2023)
This work aims to investigate communication practices at work and their direct effects on the quality of interpersonal relationships in professional environments. This is a quantitative research with Large-N sampling, applied in two stages in the municipality of Tangará da Serra-MT, in 2022 and 2023, a random sample of 724 workers of the retail trade and service companies of the municipality. The results indicate that the professionals are unaware of their communicative capacities and limitations, constantly attributing to others the causes of internal conflicts. In addition, most workers recognized as positive their interactions with the managers of the company, clearly informing the tasks and attributions of the position in most of the moments of communication, with a tendency to cooperation as a dynamic most practiced at work. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-114